Acute bacterial diarrhoea in the emergency room: therapeutic implications of stool culture results. Issue 3 (September 1994) - Kaminski, N; Bogomolski, V; Stalnikowicz, R
Abstract : Empiric treatment with ciprofloxacin and norfloxacin has been recommended recently for patients with acute diarrhoeal disease. In a retrospective 6-month study period the results of stool cultures from 209 patients with acute diarrhoea admitted to the emergency room were analysed. Seventy-eight cultures (37%) were positive for one or more bacteria. Shigella was the most commonly isolated pathogen (68%). Shigella sonnei comprised 72% and Shigella flexneri 19% of all the bacterial isolates. While no antimicrobial resistance to ciprofloxacin was found for both Shigella species, only 36 and 26% of the Shigella isolates were sensitive to ampicillin and trimethoprim-sulfamethoxazole (TMP-SMZ), respectively. These findings point out to the emergence of drug resistance to commonly used antimicrobial drugs. Shigella's high sensitivity to the newer quinolones should make this the treatment of choice for the very sick patient, although physicians should be cautioned to the fact that indiscriminate use of this drug could result in the emergence of resistance similar to that noted with ampicillin and TMP-SMZ.